Prolonged and Controllable Release of Doxorubicin Hydrochloride from the Composite Electrospun Poly(ε-Caprolactone)/Polyvinylpyrrolidone Scaffolds - Goreninsky (Goreninskii) S. I. Semen Igorevich; Volokhova A. A. Apollinariya Aleksandrovna; Frolova A. A. Anastasiya Aleksandrovna; Buldakov M. A. Mikhail Aleksandrovich; Cherdyntseva N. V. Nadezhda Viktorovna; Choynzonov E. L. Evgeny Lkhamatsyrenovich; Sudarev E. A. Evgeniy Aleksandrovich; Filimonov V. D. Viktor Dmitrievich; Tverdokhlebov S. I. Sergei Ivanovich; Bolbasov E. N. Evgeny Nikolaevich (2023, 2023)
Title screen